2014
DOI: 10.1155/2014/492679
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Detection, Grading, and Growth Behavior Evaluation of Subthreshold and Low Intensity Photocoagulation Lesions by Optical Coherence Tomographic and Infrared Image Analysis

Abstract: Purpose. To correlate the long-term clinical effect of photocoagulation lesions after 6 months, as measured by their retinal damage size, to exposure parameters. We used optical coherence tomographic (OCT)-based lesion classes in order to detect and assess clinically invisible and mild lesions. Methods. In this prospective study, 488 photocoagulation lesions were imaged in 20 patients. We varied irradiation diameters (100/300 µm), exposure-times (20–200 ms), and power. Intensities were classified in OCT images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The classes can also be used to improve the characteristic damage threshold algorithms and enable subvisible thermal laser treatment of the retina with a temperature based and, thus, objectively defined dosage. 27,28 Clinical studies are necessary in . This is an aberration from the goal to achieve lesions of uniform size.…”
Section: Discussionmentioning
confidence: 99%
“…The classes can also be used to improve the characteristic damage threshold algorithms and enable subvisible thermal laser treatment of the retina with a temperature based and, thus, objectively defined dosage. 27,28 Clinical studies are necessary in . This is an aberration from the goal to achieve lesions of uniform size.…”
Section: Discussionmentioning
confidence: 99%
“…These changes, however, may show a temporal delay. The retinal structural changes may not be visible on early OCT images, but are visible on the follow-up images 9. Koinzer et al have documented an OCT-based classification of laser-induced retinal morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…In their recent study, Koinzer at al. [2] reported first detectable changes 2h after treatment with an increased scattering to be located in the neuronal retina. However, when applying lasers for retinal treatment, the melanin in the RPE acts as the main absorber of commonly used treatment lasers emitting in the green and yellow spectral range [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an ophthalmoscopic assessment of the laser coagulation effects in deeper retinal layers is not possible. Recent studies by Koinzer et al [2] have shown that ophthalmoscopic analysis of laser coagulation burns may be misleading regarding effective laser lesion size and total affected tissue area.…”
Section: Introductionmentioning
confidence: 99%